2020
DOI: 10.1158/1078-0432.ccr-19-3402
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Antitumor Effect of Apalutamide with Abiraterone Acetate plus Prednisone in Metastatic Castration-Resistant Prostate Cancer: Phase Ib Study

Abstract: Purpose: Apalutamide is a next-generation androgen receptor (AR) inhibitor approved for patients with nonmetastatic castrationresistant prostate cancer (CRPC) and metastatic castrationsensitive prostate cancer. We evaluated the pharmacokinetics, safety, and antitumor activity of apalutamide combined with abiraterone acetate plus prednisone (AA-P) in patients with metastatic CRPC (mCRPC).Patients and Methods: Multicenter, open-label, phase Ib drugdrug interaction study conducted in 57 patients with mCRPC treate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…24 In that study, the primary end point was rPFS, which was longer in the combination arm ( ACIS did not include a pharmacokinetic component, although an earlier phase I study observed no significant pharmacokinetic interaction between abiraterone and apalutamide. 25 Our data, however, raise the possibility that a pharmacokinetic effect may be at play, if examined in a larger and more robust study. The same might apply to the PLATO trial, in which men who had been treated with enzalutamide as first-line treatment for mCRPC were randomly assigned to receive either enzalutamide plus AAP or placebo and AAP in the second-line setting.…”
Section: Discussionmentioning
confidence: 67%
“…24 In that study, the primary end point was rPFS, which was longer in the combination arm ( ACIS did not include a pharmacokinetic component, although an earlier phase I study observed no significant pharmacokinetic interaction between abiraterone and apalutamide. 25 Our data, however, raise the possibility that a pharmacokinetic effect may be at play, if examined in a larger and more robust study. The same might apply to the PLATO trial, in which men who had been treated with enzalutamide as first-line treatment for mCRPC were randomly assigned to receive either enzalutamide plus AAP or placebo and AAP in the second-line setting.…”
Section: Discussionmentioning
confidence: 67%
“…We chose studies from the ClinicalTrial database and EudraCT database and some retrospective studies from the NCBI database published in the last 5 years. The selected studies explored the effect of dexamethasone (70)(71)(72)(73)(74)(75)(76), prednisone (77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93), and prednisolone (94) (see Table 2).…”
Section: Clinical Trials In Last 5 Yearsmentioning
confidence: 99%
“…PSA response rate: A decline of PSA ≥50%. CRPC, castration-resistant prostate cancer; PSA, prostate-specific antigen; PFS, progression free survival; OS, overall survival; po, oral; QD, quaque die; QAM, every morning; QPM, every evening; BID, twice daily; ivgtt, intravenous drip; ONCE, only once.docetaxel, cabazitaxel, Ra-223, orteronel, dutasteride, and apalutamide(77)(78)(79)(80)(81)(82)(83)(84)92,93,95,96). Yu et al(88) evaluated the effectiveness of intravenous apatorsen with oral prednisone (5 mg, twice daily) or prednisone alone, and observed a PSA decrease ≥50% in 47% of patients in the apatorsen with prednisone group compared to a decrease of 24% in the prednisone only group.…”
mentioning
confidence: 99%
“…Prostate cancer is the most common malignant tumor in men and ranks as the leading cause of cancer-related mortality in most countries of the world ( 1 , 2 ). Although multiple therapeutic strategies, including surgery, ADT, and chemotherapy, are initially highly effective, progression eventually occurs years later ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%